Energy Efficient DF Relay Placement in alpha-mu Fading Channel with Cooperative and Non-Cooperative Schemes - B. Ghosh; S. Biswas; A. Chandra; A. K. Mal (Radioengineering, 2016)
In this paper we examine the energy efficiency of relay aided wireless sensor network (WSN) links where the two-hop transmission between source and destination is realized with an adaptive decode and forward (DF) relay. The receiver may use only the relayed signal (non-cooperative mode) or it may be combined with the signal directly available from the source (co-operative mode). In the second mode, we have considered two combining schemes, selection combining (SC) and maximum ratio combining (MRC). A generalized alpha-mu model is used to characterize fading and spectrally efficient M-ary quadrature amplitude modulation (MQAM) is chosen as the modulation technique. The alpha-mu model is quite general in nature and it encompasses other popular fading models such as Rayleigh and Nakagami-m. The result of our analysis reveals that combining does not necessarily help in reducing energy requirement and the decision of whether 'to use' or 'not to use' combining depends on the source to destination distance. Further, a comparison between MRC and SC from the energy efficiency perspective manifests that using MRC does not automatically guarantee maximum energy savings and the SC strategy is more robust against parameter variations as well as incurs lower receiver complexity. We also investigate the optimal relay location, which minimizes energy requirement, for all the above mentioned relaying strategies, and study how different system parameters affect the optimal relay placement.